1997
DOI: 10.1074/jbc.272.40.25043
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Docking Sites of the Rat Prolactin Receptor Required for Association and Activation of Stat5

Abstract: Prolactin (PRL) interacts with a single chain prolactin-specific receptor of the cytokine receptor superfamily. PRL triggers activation of Jak2 kinase which phosphorylates the PRL receptor itself and the mammary gland factor, Stat5, a member of the family of signal transducers and activators of transcription (Stat). Selection of the particular substrate (Stat 5), that is characterized by transcriptional responses to PRL, has been shown to be determined by specific tyrosine-based motifs common to many cytokine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 49 publications
7
50
0
Order By: Relevance
“…Further receptor systems in which a tyrosine-based STAT5 recruitment has been shown include the growth hormone receptor (40 -42), erythropoietin receptor (43)(44)(45) and the IL-2 receptor ␤-chain (46). Particularly, the similarity with a STAT5-binding motif within the erythropoietin receptor (Tyr 431 ) LKYLYLVVS is remarkable (47). Interestingly, the double tyrosine motif is not conserved between man and mouse.…”
Section: Discussionmentioning
confidence: 95%
“…Further receptor systems in which a tyrosine-based STAT5 recruitment has been shown include the growth hormone receptor (40 -42), erythropoietin receptor (43)(44)(45) and the IL-2 receptor ␤-chain (46). Particularly, the similarity with a STAT5-binding motif within the erythropoietin receptor (Tyr 431 ) LKYLYLVVS is remarkable (47). Interestingly, the double tyrosine motif is not conserved between man and mouse.…”
Section: Discussionmentioning
confidence: 95%
“…These results suggest that GH-dependent activation of STAT5 proteins requires binding of the STAT to one or more phosphorylated tyrosines in the cytoplasmic domain of GH receptor. A similar requirement of multiple phosphorylated tyrosine(s) in the receptor for maximal activation of STAT5 has been demonstrated for EPO, PRL, IL-2, IL-5 and granulocyte-macrophage colonystimulating factor (Damen et al, 1995;Fujii et al, 1995;Itoh et al, 1998;Pezet et al, 1997;Quelle et al, 1996;van Dijk et al, 1997).…”
Section: Mechanism Of Activation Of Stat Proteins By Ghmentioning
confidence: 95%
“…Furthermore, we determined that this tyrosine also regulates the activation of Stat5 (32). In addition, other studies have shown that the C-terminal tyrosine of the receptor regulates Stat5 recruitment to the PRLR (38). The association of SHP-2 or Stat5 to the FIG.…”
Section: Discussionmentioning
confidence: 99%